AUTOMATED TELLER MACHINES’ ADOPTION: AN APPLICATION OF THE TECHNOLOGY ACCEPTANCE MODEL (INMR - Innovation & Management Review, 2007)
The objective of this study is to evaluate the applicability of an adapted version of the Technology Acceptance Model (TAM) to the Automated Teller Machines (ATM) adoption. TAM, originally developed by Davis (1989) and later adapted by Gefen (2003) was based on the Theory of Reasoned Action (Ajzen & Fishbein, 1980) and has been broadly used to identify the antecedents to behavioral intention. Specifically, in this study it was used to analyze the relationship between habit and the two main constructs of TAM, perceived utility and perceived ease of use. Automated teller machines were chosen as object of the study because it has already been adopted by a large part of the population, making easier to evaluate the habit construct, incorporated by Gefen (2003) to the Technology Acceptance Model.